Digital Payment Adoption and Financial Inclusion in Nepal - Yadav, Dipesh (Nepalese Journal of Finance, 2025)
This study analyzed the digital payment adoption and financial inclusion in Nepal. The dependent variable is digital payment system. Similarly, the selected independent variables are social influences, technological infrastructure, and ease of use, financial literacy, and security influence. The primary source of data is used to assess the opinions of the respondents regarding social influences, technological infrastructure, and ease of use, financial literacy, and security influence in Nepal. The study is based on primary data of 165 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of digital payment adoption and financial inclusion in Nepal. The study showed that social influence is positively correlated to digital payment system. This reveals that better social influence leads to better performance of digital payment system. Similarly, technological infrastructure is positively correlated to digital payment system. This implies that technological infrastructure may have impact on digital payment system. Likewise, ease to use is positively correlated to digital payment system. It indicates that ease to use leads to better digital payment system. Moreover, financial literacy is positively related to digital payment system. It means that the financial literacy leads to increase digital payment system. Similarly, security is positively correlated to digital payment system which indicates that good security leads to better digital payment system.